Some Results in Nearly Gorenstein Numerical Semigroup of 6 Generators With Type 5 - Belgin, Ö.; Ali, Y. (Communications in Mathematics and Applications, 2022)
In this paper, some results are found in the nearly Gorenstein numerical semigroups of 6 generators with type 5. All nearly Gorenstein numerical semigroups with e generators and type \(p\) are given.
Keywords: Type of a numerical semigroup; Nearly Gorenstein; NG-vector